Factors that influence Middle East tourist to come to Malaysia. (Does Malaysia fulfill the factors needed to encourage more tourist from these area to come here) / Mohd Hafizan Che Hashim - Che Hashim, Mohd Hafizan (Faculty of Business and Management, 2009)
Factors are one that actively contributes to an accomplishment, result, or process. Nowadays, everything that a person done must have a reason on whatever they implement to do and to make it readily established. In order to study the factors, a research has been conducted whether what factors have made Middle East tourist to visit to Malaysia. In this project paper, the studies discuss about some reason that contribute to the factors of Middle East tourist to come to Malaysia which is travel trend, service efficient or not, and also the strategies by Tourism Malaysia to lure more tourist to Malaysia. From this study, research found that there is no gap in term of tourist arrival, spending, factor attracting the tourist and strategies by Tourism Malaysia to lure Middle East Tourist but there are minor gap in certain area which needs to be manage with like the challenges that Tourism Malaysia faced.